Magnetic Separation in Bioprocessing Beyond the Analytical Scale: From Biotechnology to the Food Industry - Schwaminger, Sebastian P.; Fraga-García, Paula; Eigenfeld, Marco; Becker, Thomas M.; Berensmeier, Sonja (Frontiers in Bioengineering and Biotechnology, 2019)
Downstream processing needs more innovative ideas to advance and overcome current bioprocessing challenges. Chromatography is by far the most prevalent technique used by a conservative industrial sector. Chromatography has many advantages but also often represents the most expensive step in a pharmaceutical production process. Therefore, alternative methods as well as further processing strategies are urgently needed. One promising candidate for new developments on a large scale is magnetic separation, which enables the fast and direct capture of target molecules in fermentation broths. There was a small revolution in this area in the last ten to twenty years and a few papers dealing with the use of magnetic separation in bioprocessing examples beyond the analytical scale have been published. Since each target material is purified with a different magnetic separation approach, the comparison of processes is not trivial but would help to understand and improve magnetic separation and thus making it attractive for the technical scale. Thus, to address this issue, we report on the latest achievements in magnetic separation technology and offer an overview of the progress of the capture and separation of biomolecules derived from biotechnology and food technology. Magnetic separation has great potential for high-throughput downstream processing in applied life sciences. At the same time, two major challenges need to be overcome: (1) the development of a platform for suitable and flexible separation devices and (2) additional investigations of advantageous processing conditions, especially during recovery. Concentration and purification factors need to be improved to pave the way for the broader use of magnetic applications. The innovative combination of magnetic gradients and multipurpose separations will set new magnetic-based trends for large scale downstream processing.